A Quantitative and Qualitative Analysis of the Patient and Caregiver’s Perspective on Outcomes of Intravenous Administration of Low-Dose Ketamine for C-PTSD, TBI, and Treatment Resistant MDD: A Clinical Example - Laura Hentig; James Hentig; Jessica M. Gill (Reports)
Background and Clinical Significance: Treatment resistant psychiatric disorders affect millions of people across the globe. Ketamine has been employed as a treatment option for those with treatment resistant depression, as well as for chronic pain and alcohol use disorder. However, case presentations and research has been limited on the outcomes, and furthermore there is even less on the patient or caregiver perspective on the impact of the treatment. Case Presentation: Here, we present a middle-aged male who has undergone 20 intravenous (IV) ketamine infusions to treat Complex Post-Traumatic Stress Disorder (C-PTSD) and Major Depressive Disorder (MDD). We provide both qualitative perspectives from the patient, caregiver, as well as quantitative analyses of the patient from the Patient Health Questionnaire-9 (PHQ9), Beck’s Depression Inventory (BDI), and the Neurobehavioral Symptom Inventory (NSI) following treatment and weekly (4 weeks) assessments between treatments. Conclusions: Collectively, these data provide a holistic view of the use of ketamine for this patient on a variety of mental health, physiological, and behavioral conditions.